Analisis Analisis Hambatan Komunikasi Karyawan Lokal di Kalimantan Barat - Theresia Intan (Institut Pertanian Bogor, 2020)
This research focuses on upward communication barriers at PT. Hutan Ketapang Industri. This is because at PT. Hutan Ketapang Industri there are differences in the status of staf and non staf employees (the name for native local employees of Kalimantan residents). Local employees are the surrounding community residing in the concession area who work at PT. HUTAN KETAPANG INDUSTRI, the community around the concession area has several different ethnic groups. This research uses quantitative methods, data collection techniques through questionnaire surveys. Measurement of communication barriers refers to six types of barriers namely: (1) technical barriers, (2) behavioral barriers, (3) language barriers, (4) structural barriers, (5) distance barriers, (6) background barriers. the sample selection in this study uses simple random sampling. The research method with survey, data collection techniques using a questionnaire to 95 local employees. From the statement that was distributed, it was found that there were distance and language barriers of PT. Hutan Ketapang Industri.